Development of a Nine-Language Dictionary as a Communication Facilitator between Merchants and Tourists at the Airport - Agustina Agustina; Ramli Ramli; Ahyar Ahyar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
Communication between local merchants and foreign tourists at Bima Airport is often hindered by language barriers, which may affect the convenience and smoothness of transactions. This study aims to develop a nine-language dictionary application capable of translating Indonesian into nine foreign languages: English, Malay, Korean, Hindi, Italian, Afrikaans, German, Japanese, and Arabic, which is feasible, practical, and effective. The method used was Agile with a Scrum model approach, allowing for iterative and user-responsive application development. Surveys and interviews were conducted to identify the necessary features, such as text and voice translation. The trial results indicate that the application is effective in reducing communication barriers, with respondents giving positive feedback and a score of 90.52%, suggesting that the application is highly helpful in facilitating transactions. This application is designed to promote more effective communication, enhance merchants’ confidence, and support the tourism sector in Bima. With a simple and user-friendly approach, the nine-language dictionary application is expected to serve as a practical solution to overcome language barriers, improve service quality, and strengthen interactions between the local community and tourists